Maternal weight gain management during pregnancy: A scoping review - Metty Tsabitah Aziz; Ismarwati (Universitas Aisyiyah Yogyakarta, 2025)
Background: Unhealthy weight gain during pregnancy can result in adverse outcomes for both mother and baby. Globally, there are 6,400 neonatal and 800 maternal deaths every day. To reduce maternal and neonatal mortality rates, it is imperative to enhance the health condition by effectively regulating weight gain throughout pregnancy. Objective: This study aimed to identify scientific evidence on managing maternal weight gain during pregnancy. Methods: This scoping review used the five steps outlined by Arksey and O'Malley and adhered to the Prisma-ScR checklist. This study used the population, concept, and context (PCC) framework. The article searches used EBSCO, Science Direct, and PubMed databases. The inclusion criteria applied were original studies written in English published from 2018 to 2023, full-text articles, and articles that discussed maternal weight gain management during pregnancy. The exclusion criteria applied were review articles and articles with research data collected before 2013. The critical appraisal tools used were the Joanna Briggs Institute (JBI) and Mix Methods Appraisal Tools (MMAT). Results: Based on this review, the authors identified that behavioral change interventions were crucial as a foundation for more extensive interventions to achieve standard maternal weight gain during pregnancy. Several interventions for managing weight gain during pregnancy include setting weight gain goals, daily weighing, exercise, counseling on healthy lifestyle, multi-interventions, and a combination of technologies. Conclusion: Behavior modification and some interventions can enhance success in achieving the standard weight gain during pregnancy. Integrating weight management into routine antenatal care is essential for strengthening maternal and fetal health.